Chromatin structure is required to block transcription of the methylated herpes simplex virus thymidine kinase gene. - Buschhausen, G (1987)
Inhibition of herpes simplex virus (HSV) thymidine kinase (TK) gene transcription (pHSV-106, pML-BPV-TK4) by DNA methylation is an indirect effect, which occurs with a latency period of approximately equal to 8 hr after microinjection of the DNA into TK- rat 2 and mouse LTK- cells. We have strong evidence that chromatin formation is critical for the transition of the injected DNA from methylation insensitivity to methylation sensitivity. Chromatin was reconstituted in vitro by using methylated and mock-methylated HSV TK DNA and purified chicken histone octamers. After microinjection, the methylated chromatin was always biologically inactive, as tested by autoradiography of the cells after incubation with [3H]thymidine and by RNA dot blot analysis. However, in transformed cell lines, reactivation of the methylated chromatin occurred after treatment with 5-azacytidine. Furthermore, integration of the TK chromatin into the host genome is not required to block expression of the methylated TK gene. Mouse cells that contained the pML-BPV-TK4 chromatin permanently in an episomal state also did not support TK gene expression as long as the TK DNA remained methylated.